Tseng's methods for inclusion problems on Hadamard manifolds. (9th December 2022) - Khammahawong, Konrawut; Kumam, Poom; Chaipunya, Parin; Martínez-Moreno, Juan
Abstract : In this article, we present two Tseng's methods for finding a singularity point of an inclusion problem which is defined by means of a sum of a single-valued vector field and a multivalued vector field on a Hadamard manifold. Under standard assumptions, we prove any sequence generated by the proposed methods converges to a singularity point, whenever it exists. Moreover, applications to convex minimization problems and variational inequality problems are provided.